Pengaruh Edukasi Penanganan Awal Hipotermia Dengan Booklet Terhadap Tingkat Pengetahuan Pada Pendaki Gunung Prau - Ningsih, Aditiana; Isnaini, Nur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: The purpose of this study was to determine the effect of early hypothermia handling education with booklets on the level of knowledge in prau mountaineers.Method: This research is Pre-Experimental, the design used in this study is One Group Pretest-Posttest Design. Respondents used were Gunung Prau climbers with a large sample of 34 respondents with a sampling technique using accidental sampling technique. The instrument in this study used a questionnaire about hypothermia. Data analysis uses Paired Sample T-Test.Results: The average value of respondents' knowledge before being given education with a booklet of 12.74 + 1.746 and after 15.74 + 1.189 with an average difference of -3,000 + 1,128 and obtained a significance value of 0.001 (p-value <0.005).Conclusion: Providing education on the initial handling of hypothermia with booklets provides an influence in increasing knowledge in mountain climbers prau.